The Story of Earth An Observational Guide - Hauptvogel, Daniel; Sisson, Virginia (Open textbook library., 2021)
Our goal in creating the material for this lab manual was to focus heavily on students making observations of geologic data, whether rocks, minerals, fossils, maps, graphs, and other things. We want students to look at things and wonder why, how, and when. The exercises and examples used in this book are scattered throughout the world. We wanted to make sure that one region of the world was not the sole focus of this work.